Implementation of Online E –Auction to Overcome the Problem of Corruption with Effective and Efficient Procurement with Transparency (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research paper explores the concept of e-Auction, an increasingly form of online procurement. There is fixed delivery policy. This is a fully dynamic system which can be easily operated by the users. This research paper explores all the increasing form of online procurement. Online e auction system is gaining popularity day by day because of its ease of making online bidding and selling or buying. Users can freely go the website and register there and it’s ready for selling or buying their product. The main thing that is needed to be there is trust among the users, so that they can easily register and take part in the process without having any doubt regarding security. The aim of any online system are related with two points that are: 1.Customer satisfaction 2.Business purpose. Therefore, to meet these requirements there must be need of making enhancements in the online auction system. This paper will explore the all forms of online procurement that we can make to improve the current system.